Geoenvironmental engineering - Mohamed, Abdel-Mohsen Onsy (Elsevier, 1998)
The new social and economic era calls for integration of ecology and economy in a system of cause and effect. The central element in this shift is sustainable development. Fundamental to the achievement of sustainable development is the requirement for environmentally responsible waste management and restoration of the environment. Solutions to the complex problems confronted by waste management and environmental restoration industry are currently handled by the geoenvironmental engineering profession that needs a good background in soil biology, chemistry, mechanics, mineralogy, and physics. In recognition of this need, this book summarizes relevant aspects of various soil physics, mineralogy, and chemistry as well as the chemistry of pollutants. This treatment will provide sufficient background to students and practicing engineers to enable them to think about how to approach waste management and environmental restoration problems.
Keywords: Environmental geotechnology.; elektronické knihy; electronic books